Clinical Outcomes of Cyanoacrylate Closure Versus Radiofrequency Ablation for Saphenous Varicose Veins: A Single-Center Retrospective Study - Yuki Kamikawa; Takeshi Kinoshita; Yosuke Saito; Tetsuma Oyama; Minoru Tabata; Hirotaka Inaba (International Journal of Vascular Medicine)
Conclusion: CAC is a viable alternative to RFA, demonstrated equivalent occlusion rates, though CAC exhibited a higher incidence of phlebitis. Careful patient selection and perioperative management may help mitigate risks. Further studies with larger cohorts and longer follow-up are needed to optimize treatment protocols and long-term outcomes.